2022
DOI: 10.1021/acsnano.2c10092
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary Phonon Displacement and Giant Resonance Raman Enhancement in WSe2/WS2 Moiré Heterostructures

Abstract: Twisted van der Waals heterostructures are known to induce surprisingly diverse and intriguing phenomena, such as correlated electronic phase and unconventional optical properties. This can be realized by controlled rotation of adjacent atomic planes, which provides an uncommon way to manipulate inelastic light–matter interactions. Here, we discover an extraordinary blue shift of 5–6 wavenumbers for high-frequency phonon modes in WS2/WSe2 twisted heterobilayers, captured meticulously using Raman spectroscopy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…65–68 According to previous study, the WSe 2 /WS 2 vdW heterostructure with C7 stacking is the most stable configuration. 35,37,38,65,69,70 Thus, we focus on C7 configuration in this study, while our test calculations on other geometries like T stacking demonstrate that molecule intercalation would not change the sequence of energies for the bilayer heterostructures. In order to reduce the lattice mismatch, the lattice constant of the WSe 2 /WS 2 heterostructure is set to be the average value of the lattice constants of WSe 2 and WS 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…65–68 According to previous study, the WSe 2 /WS 2 vdW heterostructure with C7 stacking is the most stable configuration. 35,37,38,65,69,70 Thus, we focus on C7 configuration in this study, while our test calculations on other geometries like T stacking demonstrate that molecule intercalation would not change the sequence of energies for the bilayer heterostructures. In order to reduce the lattice mismatch, the lattice constant of the WSe 2 /WS 2 heterostructure is set to be the average value of the lattice constants of WSe 2 and WS 2 .…”
Section: Resultsmentioning
confidence: 99%
“…[23][24][25][26] Due to the robust type-II band alignment, WSe 2 /WS 2 vdW heterostructure has attracted considerable attention. [27][28][29][30][31][32][33][34][35][36][37][38] In vertical heterostructures, the vdW gap between monolayer components offers space for the intercalation of ions and molecules, thereby giving rise to new opportunities for property modulation. It has been evidenced that ion intercalation into TMD heterostructures has a significant impact on the chemical and physical properties and leads to broad applications in energy storage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the researchers also concluded that twist angle can lead to a large enhancement in Raman vibrational intensity which has been demonstrated for the first time in TMD heterostructures. 382 Moiréphonons exhibit a high degree of complexity, challenging to attribute specific peaks to phonons in bilayer TMDs. This complexity is further compounded in the case of folded modes, which are highly influenced by moirésuperlattices.…”
Section: High-frequency Modesmentioning
confidence: 99%
“…[5,6] The advent of 2D materials eliminated many of these compatibility constraints, [7] with micromechanical stacking allowing the integration of 2D crystals with different structures and large lattice mismatch [8,9] and opening up additional degrees of freedom such as interlayer twist. [10][11][12] Different 2D [13][14][15][16] and thicker van der Waals crystals [17,18] can also be stitched into lateral heterostructures with covalent interfaces embedded in each of the layers. [19] Heterostructures have also been formed from low-dimensional structures, notably nanowires where both the axial [20][21][22][23] and radial [24,25] integration of different materials has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%